Effects of IL-6 Polymorphisms on Individual Susceptibility to Allergic Diseases: A Systematic Review and Meta-Analysis - Yang, Ying; Xiao, Jingxin; Tang, Lingling; Wang, Bohan; Sun, Xianhong; Xu, Zhongchi; Liu, Li; Shi, Suofang (Frontiers in Genetics, 2022)
Background: Many studies have assessed the potential link between interleukin-6 polymorphisms and susceptibility to allergic diseases. However, the results are still conflicting. Therefore, a comprehensive meta-analysis can not only resolve differences but also provide clues for future projects. Methods: A systematic electronic search was conducted on the databases of Web of Science, PubMed and Cochrane Library to retrieve all published studies. Revman and Stata software were used for statistical analysis. Results: This meta-analysis included 11 studies. The results revealed that there was no statistically significant correlation between IL-6 polymorphisms with allergic diseases risk in general population. Subgroup analyses demonstrated that rs1800795 affected allergic diseases risk in different populations. Conclusions: Our findings suggested that IL-6 rs1800795 was associated with allergic diseases susceptibility among Asians and Caucasians in opposite trends, and it might influence the risk of asthma and allergic rhinitis. None of IL-6 polymorphisms were shared risk variants of allergic diseases.